Formulation and Evaluation of Antimicrobial Activities of Herbal Cream Containing Ethanolic Extracts of Azadirachta indica Leaves and Aloe Vera Gel - Chukwuemeka Paul Azubuike,; Sandra Ebele Ejimba,; Abel Olusola Idowu ,; Issac Adeleke, (Journal of Pharmacy and Nutrition Sciences, 2015)
The antimicrobial activity of ethanolic extract of dried leaves of Azadirachta indica (Neem), fresh gel of Aloe vera, combination of the two extracts and the creams formulated with these extracts were evaluated. The preliminary in vitro antimicrobial activity of the extracts at various concentrations and those of their creams were determined against some microorganisms using the agar cup plate method. The growth inhibition zones of the extracts on the microorganisms were noted. The minimum inhibitory concentration (MIC) was also determined by agar dilution method. The physical properties of the creams formulated with these extracts were evaluated using standard procedures. Gram positive bacteria were more susceptible to Neem extract of which Staphylococcus aureus was the most susceptible with the lowest MIC value (2.5mg/ml). The fungal strain Candida albicans had the lowest MIC value (2.0mg/ml) for the Aloe vera gel extract. The MIC values (mg/ml) of Neem leaves against Bacillus subtilis, Escherichia coli, Staphylococcus aureus, Pseudomonas aeroginosa, Candida albicans and Aspergillus niger were 5.00, 5.00, 2.50, 10.00, 2.50, 5.00 respectively, while MIC of Aloe extract were 8.00, 8.00, 4.00, 8.00, 2.00, 4.00 respectively. Among the formulated creams, the formulation containing equal concentrations of the extracts (1:1) showed the highest antimicrobial activity, however the commercial brand Funbact A® had better antimicrobial activity. Most of the creams showed comparable physical properties. The study showed that the creams containing equal concentrations of the two ethanolic extracts have high potentials as topical antimicrobial agents especially against skin infections due to the tested Gram positive bacteria and Candida albicans.